Case reportHereditary haemorrhagic telangiectasia in a patient taking anticoagulant drugs who has sustained facial trauma - Kamiński, Bartłomiej; Błochowiak, Katarzyna; Olek-Hrab, Karolina; Sokalski, Jerzy; Witmanowski, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
The authors present the case of a 41-year-old patient with hereditary hemorrhagic telangiectasia (HHT), who in the past had an aortic valve replacement surgery, currently takes anticoagulant drugs and has sustained an extensive trauma to the nose as a result of a dog bite. The HHT is diagnosed basing on the presence of at least three out of four symptoms or signs: spontaneous epistaxis, vascular lesions in the internal organs, skin telangiectasias and a family history of the disease. The presented patient showed hepatic angioma, history of recurrent bleeding from the tongue and spontaneous epistaxis as well as numerous skin telangiectasias. In his case, HHT coincided with chronic treatment with coagulants implemented after an implantation of the artificial aortic replacement valve, what substantially modified the clinical picture and course of treatment.